A fully electronically controllable Schmitt trigger and duty cycle‐modulated waveform generator. (5th January 2017) - Kumar, Atul; Chaturvedi, Bhartendu; Maheshwari, Sudhanshu
Summary: The paper introduces a new Schmitt trigger consisting of only one multiple‐output current inverting differential input transconductance amplifier with no passive element. The proposed circuit is simple and usable up to 100 MHz with the advantage of electronically controlled threshold levels and amplitude of the output. The circuit is also little sensitive to temperature and benefits from low power dissipation (0.5 mW). The amplitude of the output current is tunable electronically from 5 nA to 500 μA, which is a wide tunable range. The effects of transistors mismatch on proposed Schmitt trigger have also been explored. The utility of the proposed circuit is further justified through its application as a triangular/square wave generator, with a maximum frequency of 75 MHz. Duty cycle modulation through electronic means is also shown for the generator circuit, where duty cycle results for 80, 20, and 95% have been included, by varying external control current. The cadenceVIRTUOSO simulation results by using generic process design kit 90‐nm technology are shown to confirm the proposed theory. The proposed circuits are also verified through experimental results by using commercial integrated circuits: AD844 and LM13700. All the simulated and experimental results promise potential applications of the proposed circuits in instrumentation and communication systems. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : The paper introduces a new Schmitt trigger consists of only one multiple‐output current inverting differential input transconductance amplifier (MO‐CIDITA) with no passive element. The proposed circuit is simple and usable up to 100 MHz, with the advantage of electronically controlled threshold levels and magnitude of the output. The utility of proposed circuit is justified through its application as triangular/square wave generator. Both the proposed circuits are verified through simulation and experimental results and promise potential applications in instrumentation and communication systems.